A framework for future development of the fertilizer industry in South Vietnam - Tran Quang Minh; Sharif, M. N.; Pakorn Adulbhan; Woo, Wai-Ling; Government of Netherlands (Bangkok : Asian Institute of Technology, 1975)
In this study, a framework for future development of the fertilizer industry in South Vietnam is studied. Firstly, an industrial development situation and the overall economic development in South Vietnam is briefly reviewed. This review, specifically, attempts to give an idea or a framework of the present state of the manufacturing sector, generally, on the overall economic development situation. Further, it also attempts to point out the importance of fertilizer on the agricultural development with respect to South Vietnam conditions. Moreover, the present state of the fertilizer industry is also briefly considered, and more important, the availability of raw-materials needed for the development of the fertilizer industry. Secondly, an econometric model is used to construct a demand function for fertilizer in order to study the demand in South Vietnam. Multiple Regression analysis is used in this problem to find out the correlation between the variables in the model, and a computer programme is used to solve the problem on a CDC 3600 computer using FORTRAN. Thirdly, the linkage effect of the development of the fertilizer industry with other sectors is also briefly studied to emphasize the importance of the fertilizer industry on the National Economic Development Situation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Fertilizer industry -- Vietnam